1986
DOI: 10.4141/cjss86-026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Large Broadcast and Small Annual Seed-Placed Phosphorus Treatments on Yield and Phosphorus and Zinc Contents of Wheat on Chernozemic Soils

Abstract: . 1986. Comparison of single large broadcast and small annual seed-placed phosphorus treatments on yield and phosphorus and zinc contents of wheat on Chernozemic soils. Can. J. Soil Sci. 66:237-248.Yield and P and Zn contents of wheat from plots on a Dark Brown Chernozemic clay soil which received single broadcast P applications and annual seed-placed P applications were compared in a 6-yr study. Broadcast P applications of20, 40, 80 and 160 kg P hs-, increased the average yield by 9, 24, 33 and 35Vo, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…This lack of P practice × location × year interaction, both with and without tillage, for yield, and for all P concentration and content variables, confirms that maintenance of high soil test P for corn is not likely to be economically justified for the 40.0 to 43.0° latitude range for elevations of < 1000 m asl. The value of maintaining high STP may be greater for higher latitudes (Wagar et al, 1986;Randall, 2009), and maybe for higher elevations.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of P practice × location × year interaction, both with and without tillage, for yield, and for all P concentration and content variables, confirms that maintenance of high soil test P for corn is not likely to be economically justified for the 40.0 to 43.0° latitude range for elevations of < 1000 m asl. The value of maintaining high STP may be greater for higher latitudes (Wagar et al, 1986;Randall, 2009), and maybe for higher elevations.…”
Section: Discussionmentioning
confidence: 99%
“…By placing fertiliser instead of incorporating it throughout the soil the available P is being put where the root system is going to grow hoping to ensure early plant P uptake and a more successful crop. Hence Wager et al (1986) found that P fertilizer application rates could be halved by placing fertiliser instead of incorporation because the applied P was more efficiently used. However, optimal fertiliser and cultivation methods depend on the initial soil P condition/ distribution (Randall and Hoeft 1988); this includes at the depth at which existing P is initially available within the soil (Heppell et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As the plant root system grows, it accesses more P from the bulk soil and less from a fertilizer band (Kalra and Soper, 1968). Lack of late‐season P supply on severely depleted soils may reduce maximum yield even with high rates of seed‐placed P (Wagar et al, 1986a). Some studies in wheat and corn indicate that foliar application of P may provide a benefit as a top‐up treatment if P uptake from seed‐placed P applications or from the soil is restricted because of moisture stress or low soil P level (Benbella and Paulsen, 1998a, 1998b; Girma et al, 2007; Green and Racz, 1999; Mosali et al, 2006).…”
Section: The 4r Package Of Management Practicesmentioning
confidence: 99%
“…In addition, the appropriate rate of application will be related to fertilizer placement and vice versa. Efficiency of use for low rates of P fertilizer is much greater with banded than broadcast fertilizers, so if low rates of P targeted to optimize yield are being used, band application is preferable (Bailey and Grant, 1990; Campbell et al, 1996a; Grant and Bailey, 1993; Karamanos et al, 2002; Wagar et al, 1986a; Wheatland Conservation Area, 2018). In contrast, if higher rates of fertilizer P are being used to build soil P, broadcast and banded applications may provide similar yields.…”
Section: The 4r Package Of Management Practicesmentioning
confidence: 99%